PELATIHAN PRAKTIKUM KIMIA SKALA KECIL: PEMBUATAN INDIKATOR ASAM BASA BERUPA BOLA ALGINAT UNGU UNTUK GURU-GURU KIMIA DI SMA SANTA FAMILIA - Harta, Johnsen; Nur Pamenang, Fransisca Ditawati; Wijayanti, Lucia Wiwid; Ratri, Monica Cahyaning; Anggreni, Viktoria Cosinta; Surianti, Yosefina Ermi; Octaviani, Laurensia (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The practicum management of chemistry teachers at senior high school on the topic of acid-base is quite good, although the majority are monotonous in testing acid-base properties using large amounts of solution. Some schools only limit the practical use of extracts from various flowers with certain color pigments, then tested on several samples and used as natural indicators, but have not paid attention to the number of reagents and estimated waste generated. The purpose of this activity is to improve the quality of classical practicum and the attractiveness of acid-base indicators from materials that refer to the principles of green chemistry. Service activities are carried out in training through the practicum method of making acid-base indicators using purple cabbage extract, sodium alginate, and 1% CaCl2 solution. This training provides a new and innovative description of the formation of purple cabbage extract gel as an acid-base indicator in the form of red balls under acidic conditions and green under alkaline conditions. Chemistry teachers were very happy and felt that this practicum was simple and interesting to be packaged and brought to the routine practicum conducted at schools.